Foundations of physical education, exercise science, and sport - Walton-Fisette, Jennifer L. 1978-; Wuest, Deborah A. (McGraw-Hill Education, 2021)
"Was physical education or anatomy and physiology one of your favorite classes? Were you a high school athlete or did you play a club sport? Are you interested in fitness, physical activity, and sport? Most importantly, are you considering a career in a human movement field such as a physical education teacher, exercise science specialist, personal trainer, or sport administrator? Then this text is for you! Come join us on this educational journey to learn about physical activity, physical education, and sport. We will provide you with the most up-to-date information while recognizing that the dynamic field of kinesiology and its disciplines are ever changing in this fast-paced, technology-driven society in which we live"--Provided by publisher.